Attaining the 2030 sustainable development goal of quality education - Birdthistle, Naomi; Hales, Rob (Family businesses on a mission, 2022)
Attaining the 2030 Sustainable Development Goal of Quality Education focuses on Sustainable Development Goal number four (SDG4): Quality Education for All. Examining family businesses in Australia, USA, Austria and Algeria, each case study presents a unique perspective from their respective country, analysing how SDG4 translates into ensuring inclusive, equitable quality education, and promoting lifelong learning opportunities for all. The case studies presented generate insights and key takeaways into the role of family businesses in providing quality education for all. The United Nations' (UN) Sustainable Development Goals (SDGs) are 17 Goals pledged by 193 nations in 2015 which would help engender an improved, fairer, and more sustainable world - one in which 'no one is left behind'. The SDGs are a call to action, to develop innovative solutions to the most complex, societal, and environmental global challenges. In Family Businesses on a Mission, series editors Naomi Birdthistle and Rob Hales bring together international case studies to illustrate how family businesses can attain the UN 2030 SDGs. Accessible to those working in the field beyond academia - such as family business practitioners, family business owners, government and policymakers, members of NGOs, business associations and philanthropic centres - the book series equally appeals to those with a general interest in entrepreneurship and business.